A Study of Customer Satisfaction on After Sales Service of Two Wheelers in Kathmandu Valley - Giri, Sanjupa; Thapa, Kumar (Journal of Business and Social Sciences Research, 2018)
The purpose of this study is to explore the relationship between various identified after-sales service attributes of Two Wheeler brands and customer satisfaction. It further intends at segregating the major after sales service as per Kano Model. This research is a quantitative research with a sample size of 280, 40 each on the basis of brands of bike and scooter. Sample is selected in a quota and convenience basis. The brands which are taken as samples includes Honda, Hero, Bajaj, Mahindra, Yamaha, Royal Enfield and others (TVS, Suzuki and VR). Kano Model analysis, frequency analysis, correlation, ANOVA test, independent sample t-test, etc. are used for data analysis. Kano model is taken as a basic model for the study. Surprisingly, it is found that supporting after sales service has more impact on customer satisfaction than major after sales services have. Apparently, the most valued after sales service is behaviour of technicians which has the strongest and positive relation with customer satisfaction. Behaviour attributes play major role in customer satisfaction. Likewise, functional and dysfunctional questions are analyzed to carry out Kano Model Analysis. From the research, it is found that Spare part supply, Warranty, Bike wash and Service camp are the must be requirements. Likewise, Repair and Maintenance, Customer Care, Inspection and Mobile Van (office hours) are regarded as one dimensional services. And, Driving Orientation and 24 hours Mobile Van service are regarded as Attractive services. At present, 63% of customers are satisfied with the after sales service and 10% are very satisfied with the current after sales service. This study is significant to distributors of two wheelers and parent companies, as they can formulate after sales service strategies by understanding the present satisfaction level of customers and degree of each after sales service attributed to satisfy the customers. Journal of Business and Social Sciences Research, Vol. 1, Issue 1, pp. 1-21